PERLINDUNGAN HUKUM BAGI DRIVER GRAB YANG MENGALAMI PESANAN FIKTIF PADA ERA GIG ECONOMY - Ery Charmelita Raska; Wardani, Susilo (LPPM STIH Awang Long, 2024)
This research aims to analyze the legal relationship between Grab drivers and Grab platform in the context of gig economy in Banyumas Regency, as well as legal protection for drivers who experience fictitious orders. This research uses normative juridical and empirical juridical methods. The research data includes primary data from direct interviews with several drivers in Banyumas Regency and supported by secondary and tertiary data. The data analysis method uses qualitative analysis method. The first research result shows that the relationship between the driver and the platform arises due to a partnership agreement that gives birth to balanced rights and obligations between the parties. In practice, the relationship between drivers and platforms looks like a working relationship where there are elements of orders, wages, and work as well as relationships such as superiors and subordinates that create imbalances in the existing partnership agreement. So it looks like a pseudo-partnership relationship. When viewed in Regional Regulation Number 5 of 2021 concerning Creative Economy Development, Grab drivers are included in the type of freelancers with a partnership pattern system using a profit-sharing system regulated in article 4 and article 33. However, these rules still do not provide adequate legal protection for online ojek drivers. The second research result, legal protection for drivers who experience fictitious orders is still limited. The Grab platform provides protection by providing a reimbursement mechanism, which has been stated in the partnership agreement between the driver and the Grab platform. The unclear legal relationship between Grab drivers and the platform in the Gig Economy era in Banyumas causes weak protection for drivers who experience fictitious orders.